Serological Differentiation of Murine Typhus and Epidemic Typhus Using Cross-Adsorption and Western Blotting - La Scola, Bernard (American Society for Microbiology, 2000)
Differentiation of murine typhus due to Rickettsia typhi and epidemic typhus due to Rickettsia prowazekii is critical epidemiologically but difficult serologically. Using serological, epidemiological, and clinical criteria, we selected sera from 264 patients with epidemic typhus and from 44 patients with murine typhus among the 29,188 tested sera in our bank. These sera cross-reacted extensively in indirect fluorescent antibody assays (IFAs) against R. typhi and R. prowazekii, as 42% of the sera from patients with epidemic typhus and 34% of the sera from patients with murine typhus exhibited immunoglobulin M (IgM) and/or IgG titers against the homologous antigen (R. prowazekii and R. typhi, respectively) that were more than one dilution higher than those against the heterologous antigen. Serum cross-adsorption studies and Western blotting were performed on sera from 12 selected patients, 5 with murine typhus, 5 with epidemic typhus, and 2 suffering from typhus of undetermined etiology. Differences in IFA titers against R. typhi and R. prowazekii allowed the identification of the etiological agent in 8 of 12 patients. Western blot studies enabled the identification of the etiological agent in six patients. When the results of IFA and Western blot studies were considered in combination, identification of the etiological agent was possible for 10 of 12 patients. Serum cross-adsorption studies enabled the differentiation of the etiological agent in all patients. Our study indicates that when used together, Western blotting and IFA are useful serological tools to differentiate between R. prowazekii and R. typhi exposures. While a cross-adsorption study is the definitive technique to differentiate between infections with these agents, it was necessary in only 2 of 12 cases (16.7%), and the high costs of such a study limit its use.